Reflections on Indo-Iranian relations - Zekrgoo, Amir Hossein (New Century Publications, 2011)
Indo-Iran relations have been the subject of intense debates and discussions in recent years, particularly post-9/11 period. The growing Indo-US relations are considered to have cast a shadow on Indo-Iran ties. Given the anti-Iranian thrust in US foreign policy, particularly on nuclear issue, the Indian foreign policy faces a daunting task of maintaining a balanced outlook towards Iran. It is in this background that this book discusses the whole gamut of issues in Indo-Iran relations including energy security, military and defence co-operation, Iranian nuclear programme, terrorism, commerce, and political, economic and cultural ties. These dimensions of Indo-Iran relations are examined with reference to the influencing factor of US, China, Pakistan, Israel, Afghanistan, and Central Asia. The 19 research articles in this volume, authored by scholars in the field, provide deep insights into the complexities of Indo-Iran relations in contemporary times in terms of their continuity, limitations, strengths and weaknesses.